The lived experiences of Filipino parentified young adults a descriptive study - Lumabi, Thea Marie E.; Moreno, Francine Gayle D.
In the Philippine context, there is an unspoken expectation for Filipinos to contribute financially to the family once they start working. Parentification is the phenomenon of role reversal between a parent and a child or the assumption of parental roles in the family. With consideration of intrinsic and extrinsic motivations, young adults uphold instrumental and emotional roles in the household. The assumption of parental roles experienced by young adults causes them to experience and fulfill their developmental tasks earlier than their peers, hence the need to examine the phenomenon. This study garnered qualitative data through in-depth interviews with 15 Filipino parentified young adults, aging 18 to 25 years old. Reflexive thematic analysis was used to analyze the data, and the themes that emerged were grounded using the Family Systems Theory. The findings showed that the experiences of parentified young adults vary from individual to individual and the family system affects the parentification experience – while some consider their parentification as beneficial, some would also consider their experiences as disruptive for their own development. With this, the parentified young adults were able to form strategies in coping with the challenges of parentification. Notably, their outlook for the future still includes fulfillment of their roles to the family. In conclusion, parentification may be considered as part of the adulting experience that it has become a norm for Filipino young adults to help their families, financially or not.